Campaigning for president 2012 : strategy and tactics - Johnson, Dennis W., 1943- (Routledge, Taylor & Francis Group, 2014)
"In this important and timely volume, Dennis W. Johnson has assembled an outstanding team of political scientists and political professionals to examine one of the fiercest and most closely fought presidential elections of our time"--Resumé vydavatele